2020
DOI: 10.1016/j.joi.2019.101005
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased evaluation of ranking metrics reveals consistent performance in science and technology citation data

Abstract: Despite the increasing use of citation-based metrics for research evaluation purposes, we do not know yet which metrics best deliver on their promise to gauge the significance of a scientific paper or a patent. We assess 17 networkbased metrics by their ability to identify milestone papers and patents in three large citation datasets. We find that traditional information-retrieval evaluation metrics are strongly affected by the interplay between the age distribution of the milestone items and age biases of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 57 publications
2
31
2
Order By: Relevance
“…If a ground truth set is available, a comparative assessment on real data is possible. This can be made more robust by considering multiple real datasets and multiple ground truth sets as done recently in (Xu et al, 2020) to compare ranking metrics for citation data. If a ground truth set is not available but a credible model for a given system exists, an assessment using synthetic data (as we have used here) is a practical alternative.…”
Section: Discussionmentioning
confidence: 99%
“…If a ground truth set is available, a comparative assessment on real data is possible. This can be made more robust by considering multiple real datasets and multiple ground truth sets as done recently in (Xu et al, 2020) to compare ranking metrics for citation data. If a ground truth set is not available but a credible model for a given system exists, an assessment using synthetic data (as we have used here) is a practical alternative.…”
Section: Discussionmentioning
confidence: 99%
“…LeaderRank is further applied to identify the influential nodes in complex products and systems (Li et al, 2019); in power grids (Zhou et al, 2019); in manufacturing services (Wu et al, 2019). Notably, in the field of "Library & Information Science", Xu et al (2020) found that LeaderRank had the best performance in ranking science and technology citation data, compared with other 17 network-based metrics. However, it is noteworthy that all the previous variants of PageRank, including LeaderRank, only consider the topological features of nodes while ignoring other non-topological features, especially the spatial features that are very important to the academic performance and impact.…”
Section: Pagerank and Leaderrankmentioning
confidence: 99%
“…This suggests that PageRank's temporal bias can be removed by rescaling the scores with a transformation that ensures that the average score of the nodes and its standard deviation are independent of node age [40]. When such a transformation is applied, the resulting 'rescaled' score can detect much earlier important nodes, with useful implications for the early detection of milestone papers [40,41], patents [41,42], and movies [43]. The benefit from this procedure is exemplified, again, by the paper that reported the first direct observation of gravitational waves [38]: the paper is ranked 16th by rescaled PageRank at the end of 2016, which constitutes a substantial improvement compared to the 12 482nd position by the original PageRank, and suggests that the paper deserves a place among the most significant ones in the APS corpus.…”
Section: Biasmentioning
confidence: 99%
“…A key challenge is that the performance of an algorithm in one of these problems does not predict its performance in another one (cross-problem variability). For example, by comparing 17 network-based ranking algorithms, a recent study [41] found that time-rescaled versions of PageRank and its variant LeaderRank [11] are the best-performing algorithms in the identification of expert-selected seminal papers and patents. PageRank is also effective in identifying influential researchers [53].…”
Section: Performance Variabilitymentioning
confidence: 99%
See 1 more Smart Citation